Is psychosocial rehabilitation useful in older people living in nursing homes? A pilot study on long‐term cognitive and behavioural outcomes. Issue 2 (11th December 2021) - De Luca, Rosaria; Maggio, Maria Grazia; Leonardi, Simona; Marra, Angela; Casella, Carmela; Calabrò, Rocco Salvatore
Abstract: Background: Age‐related changes in cognitive and behavioural functions, although common, may vary considerably across individuals and cognitive domains. There is limited evidence focusing on the benefits of training based on cognitive/social learning principles in the elderly. The aim of this study is to investigate the effects of Assertive Social Skill Training (ASST) in improving cognitive and mood outcomes in a sample of older patients living in a Sicilian nursing home. Methods: Forty‐seven older subjects were enrolled in this case–control study. Each participant was evaluated by a neuropsychologist, through the administration of a short psychometric battery using the Mini‐Mental State Examination (MMSE), Frontal Assessment Battery (FAB), and Geriatric Depression Scale (GDS), at three time points: before (T0), immediately following (T1), and 6 months after the end of the training (T2). Both groups received cognitive behavioural therapy and psychological support, but the experimental group received the ASST protocol (60 sessions, five times a week, for 12 weeks, each session lasting about 60 min), whilst the control group participated in group meetings with recreational activities. Results: Post‐hoc analysis showed that only patients receiving ASST presented a statistically significant improvement in global cognitive functions (MMSE: P < 0.001), frontal abilities (FAB: P < 0.001), and mood (GDS: P < 0.001); these positive outcomes were maintained at T2. Conclusions: Promising treatments, like the ASST, aimed at potentiating cognitive, behavioural, and social skills, are needed to improve older people's quality of life, especially when they live in nursing homes.